Hubungan antara Asupan Energi dan Asupan Lemak dengan Kejadian Obesitas pada Remaja di SMA Muhammadiyah Al-Kautsar PK Kartasura Kabupaten Sukoharjo - Saifa Adiena Nusantoro; Anisa Sekar Widhi (Universitas Pahlawan Tuanku Tambusai, 2026)
Obesity (>+2 SD) in adolescents due to long-term high energy and fat consumption risks disrupting growth and triggering cardiovascular diseases. This observational analytic study with a cross-sectional design aimed to determine the relationship between energy and fat intake and the incidence of obesity among adolescents at SMA Muhammadiyah Al-Kautsar PK Kartasura. From a population of 78 adolescents, a sample of 65 adolescents aged 16–18 years was selected. Obesity was measured using the BMI-for-age index, while dietary intake data were obtained through interviews using the SQ-FFQ questionnaire over the last 3 months. Data were analyzed using Fisher’s Exact Test. The results showed that 15 adolescents (23.1%) were obese, 15 adolescents (23.1%) had high energy intake, and 17 adolescents (26.2%) had high fat intake. There was a significant relationship between energy intake (p=0.000) and fat intake (p=0.000) with obesity. Adolescents with excessive energy and fat intake were 156 and 219 times more likely to experience obesity.